Incidence of respiratory viruses in lower respiratory tract infections in children - Crnogorac, Maja; Knezević, Aleksandra (Medicinski podmladak, 2024)
Acute viral infections of the lower respiratory tract are of great importance for mortality in children worldwide. The most common causative agents include human respiratory syncytial virus (HRSV), human metapneumovirus, parainfluenza virus, influenza virus and adenoviruses. The application of molecular methods has significantly contributed to the identification and determination of the frequency of respiratory viruses in these infections. The aim was to detect viruses that cause lower respiratory tract infections in the pediatric population using panel PCR test from a bronchoalveolar lavage samples. Eighteen samples of bronchoalveolar lavage of children younger than 5 years with a diagnosis of pneumonia and antigenic confirmation of the presence of HRSV were analyzed. Virus detection was performed by real-time chain polymerization using the commercial FTlyo ™ Respiratory Pathogens 21 kit (Fast Track Diagnostics, Luxembourg) to simultaneously detect the genomes of 18 different viruses and 1 bacterium. Respiratory viruses were detected in all 18 samples (100%). HRSV was detected in all samples (100%), human bocavirus (HBoV) in 7 (38.89%) and human rhinovirus (HRV) in one sample (5.56%). Co-infections were detected in 38,9% samples. HRSV and HBoV co-infection was proven in 33.33% samples, while the presence of all three viruses in only one sample. The results of this study show the presence of HRSV, HBoV and HRV in bronchoalveolar lavage using multiplex RT-PCR method. HRSV and HBoV was the most common viral coinfection. Additional research is needed to more accurately estimate the incidence and distribution of respiratory viruses in children.
Keywords: pedijatrija; akutna respiratorna infekcija; respiratorni virusi; multipleks RT-PCR